2012
DOI: 10.4028/www.scientific.net/msf.717-720.461
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Mobile Ions in the Presence of Charge Trapping in SiC MOS Devices

Abstract: Since power devices such as DMOSFETs will operate at high temperature where mobile ion effects are enhanced, identifying their presence is a key reliability issue for power electronics applications. We have detected the presence of mobile ion contamination in some SiC MOS device sample sets and correlated those results with observed high temperature bias instability. The differing behaviors of these devices to bias stressing as a function of temperature suggests that in some cases mobile ion drift may be count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 10 publications
1
14
0
Order By: Relevance
“…V fb hysteresis presents a counterclockwise characteristic contrary to the shift behavior at LT because of the positive shift induced by NBTS and the negative shift caused by PBTS. Similar to the explanation above, this instability behavior can be attributed to HT-activated mobile ions in SiO 2 , countering the effect of charge trapping [27,47].…”
Section: Stress Conditionssupporting
confidence: 67%
See 2 more Smart Citations
“…V fb hysteresis presents a counterclockwise characteristic contrary to the shift behavior at LT because of the positive shift induced by NBTS and the negative shift caused by PBTS. Similar to the explanation above, this instability behavior can be attributed to HT-activated mobile ions in SiO 2 , countering the effect of charge trapping [27,47].…”
Section: Stress Conditionssupporting
confidence: 67%
“…This result may be due to the introduction of mobile ions the gate oxide. These mobile ions can be activated and mobilized at an increased temperature, thereby causing an opposite effect of charge trapping in the interfacial region [41,47]. The accelerated V th recovery at HT is another possible explanation.…”
Section: Stress Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that the origin of the flatband shift is due to the charge injection from the SiC substrate into the oxide [28]. Recently, mobile charge has been detected by triangular voltage sweep (TVS) measurements and this has been identified as the cause of the instability of SiC MOS devices at elevated temperatures [29]. Nevertheless, the intrinsic mobile charge in the oxidised SiC MOS capacitors can be reduced or increased by means of the post-oxide annealing treatment [28].…”
Section: Introductionmentioning
confidence: 99%
“…Socalled fast and ultra-fast V T measurement techniques have also been utilized for structures where V T has been reduced and more sensitivity is required [12], [13]. It is widely understood and accepted that the drift is due to the well-known charge trapping phenomena at or adjacent to the SiC-SiO2 interface [14] while some researchers suspect there could still be some contribution from mobile ions [15], as was the case for early Si devices [16].…”
Section: Introductionmentioning
confidence: 99%